2008
DOI: 10.1016/j.jalgebra.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The image of the Lepowsky homomorphism for the split rank one symplectic group

Abstract: Let G o be a semisimple Lie group and let K o denote a maximal compact subgroup of G o . Let U(g) be the complex universal enveloping algebra of G o and let U(g) K denote the centralizer of K o in U(g). Also let P :be the projection map corresponding to the direct sum U(g) = (U (k) ⊗ U(a)) ⊕ U(g)n associated to an Iwasawa decomposition of G o adapted to K o . In this paper we give a characterization of the image of U(g) K under the injective antihomomorphism P : U(g) K −→ U(k) ⊗ U(a), considered by Lepowsky in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(28 citation statements)
references
References 26 publications
(41 reference statements)
0
28
0
Order By: Relevance
“…The proof of this last theorem is given in Section 8, following the ideas developed in the symplectic case. In fact, most of the results proved in Section 6 of [3] hold in this case with appropriate changes.…”
Section: Below)mentioning
confidence: 87%
See 4 more Smart Citations
“…The proof of this last theorem is given in Section 8, following the ideas developed in the symplectic case. In fact, most of the results proved in Section 6 of [3] hold in this case with appropriate changes.…”
Section: Below)mentioning
confidence: 87%
“…In [3] we proved that P (U (g) K ) = B when G 0 = Sp(n, 1), and more recently, we showed that B Wρ = B when G 0 = SO(n,1) or SU(n,1) (see [4]). Hence these results established that P (U (g) K ) = B for every classical real rank one semisimple Lie group with finite center.…”
Section: Below)mentioning
confidence: 95%
See 3 more Smart Citations